Tim Gates letter to Vernon M. Kleen regarding bird sightings, March 3, 1980 - Gates, Timet al (1980)
Field notes contributed by Tim Gates in a letter to Vernon M. Kleen, March 3, 1980. Field notes include birds sighted in the Christmas count. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1979-1980. Epson - sheet feed/flatbed